2022
DOI: 10.1097/xcs.0000000000000407
|View full text |Cite
|
Sign up to set email alerts
|

Association of Textbook Outcome and Surgical Case Volume with Long-Term Survival in Patients Undergoing Surgical Resection for Pancreatic Cancer

Abstract: BACKGROUND: Current literature has identified textbook outcome (TO) as a quality metric after cancer surgery. We studied whether TO after pancreatic resection has a stronger association with long-term survival than individual hospital case volume. STUDY DESIGN: Patients undergoing surgery for pancreatic adenocarcinoma from 2010 to 2015 were identified from the National Cancer Database. Hospitals were stratified by volume (low less than 6, medium 6 to 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…37 Multiple other studies investigating "oncological textbook outcome," showed a clear association of higher surgical case volume and better outcomes. 38 The results of this study should be interpreted in light of several limitations. First, the results of this study can be influenced by the difference in the structure of the registries, most importantly voluntary and multicenter (North America and Germany) versus mandatory and national (The Netherlands and Sweden), the frequency of auditing, and the duration of follow-up.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…37 Multiple other studies investigating "oncological textbook outcome," showed a clear association of higher surgical case volume and better outcomes. 38 The results of this study should be interpreted in light of several limitations. First, the results of this study can be influenced by the difference in the structure of the registries, most importantly voluntary and multicenter (North America and Germany) versus mandatory and national (The Netherlands and Sweden), the frequency of auditing, and the duration of follow-up.…”
Section: Discussionmentioning
confidence: 90%
“…A study including 20,902 patients after pancreatic resection derived from Medicare insurance files showed that patients after pancreatic resection by a top-quartile volume surgeon were more likely to achieve textbook outcome (70% vs 63%), whereas a resection by a low-quartile volume surgeon caused a 46% rate of textbook outcome 37 . Multiple other studies investigating “oncological textbook outcome,” showed a clear association of higher surgical case volume and better outcomes 38 …”
Section: Discussionmentioning
confidence: 99%
“…However, the association between long-term outcomes of cancer patients and surgical volume is conflicting to this day. The impact of surgical case volume on long-term survival has been extensively analyzed in hepatopancreatic and gastric cancer surgery [ 28 , 29 , 30 , 31 ]. However, the relationship between caseload and textbook outcome is still conflicting.…”
Section: Discussionmentioning
confidence: 99%
“…35 In recent years, textbook outcome measures are gaining traction across various surgical specialties, and the achievement of textbook outcome has been linked to increased survival in esophagogastric and pancreatic surgery. 36,37 Gorgec et al defined, based on an international survey among hepatobiliary surgeons, and validated TOLS, thus providing a potent outcome assessment tool in this domain. 31 Of note, the addition of the variable 'absence of a prolonged length of stay' (named TOLS +) did not reach the 80% consensus threshold in this definition, which therefore requires a more nuanced interpretation.…”
Section: A C C E P T E Dmentioning
confidence: 99%